Changing land : diaspora activism and the Irish Land War - Whelehan, Niall (Glucksman Irish diaspora series., 2021)
"Changing Land explores how the Irish Land War inspired multifaceted activism among Irish emigrants in the United States, Argentina, Scotland and England, and how diaspora activism intersected with transnational radical and reform causes"--